Enhancing the value chain in Teduh Welding towards sustaining competitive advantages / Abdul Wahab Ismail, Wan D’zlyshah Wan Shahreman and Alias Mat Ali - Ismail, Abdul Wahab; Wan Shahreman, Wan D’zlyshah; Mat Ali, Alias (2007)
The construction industry has been the thrust of the country’s development during the past twenty years. In fact, the pace of construction activities had been one of the main indicators for the state of economic conditions of this nation. After enjoying some robust and booming time during the past 1990s until 1997, the construction industry has experienced such a gloomy years starting from 1998 since the government had to cancel or defer the construction of some mega projects such as Bakun Hydro Dam in Sarawak, Ipoh-Rawang Dual Railway Track, etc. During this recession years, some construction-related companies had some difficult times which forced them to either diversify their activities or to ultimately divest some of their business activities to survive.